High-repetition rate acoustic-induced Q-switched all-fiber laser - Zalvidea, Dobryna J. V. (2005)
We report a high repetition rate actively Q switched all fiber laser. The acousto optic interaction controls the cou pling between co propagating core and cladding modes and is used to modulate the optical losses of the cavity, which permits to perform active Q-switching. Using 1.4 m of 300 ppm Er-doped fiber and a maximum pump power of 120 mW, we have obtained up to 1 W peak power pulses, with a pulse repetition rate that can be continuously varied from 1 Hz to 120 kHz and a pulse width that changes from 70 ns to 2.2 μs.